The Influence of Good Governance Implementation on Village Financial Management in Villages Receiving Regional Incentive Funds in Temanggung District - fatikhaturrohmah, aulia; Karyanti, Tutik Dwi; Al Farizi, Musyafa (Applied Accounting and Management Review (AAMAR), 2025)
This study aims to analyze the influence of implementing good governance principles on village financial management in village receiving regional incentive fund in Temanggung Regency. The examined good governance principles include accountability, transparency, participation, responsiveness, and effectiveness efficiency. The reseacrh was conducted in 11 villages that succesfully received regional inchentive fund for two concecutive years. A quantitative method with multiple linier regression analysis was employed, and data were collected through questionnaires distributed to village heads and village officials. The result indicate that the application of good governance principles has a positive (though responsiveness has a negative influence) and significant impact on village financial management. The better implementatiton leads to more optimal financial management, despite existing challenges such as limited human resource and low utilization of technology. These findings imply that village goverments should strengthen financial governance and serve as a reference for policymakers to enchance transparency and accountability.